Sport-specific balance tests account for youth alpine skiers’ ranking - Rizzato, Alex; Verdel, Nina; Paoli, Antonio; Supej, Matej; Marcolin, Giuseppe (Frontiers in Physiology, 2023)
Objective: Alpine skiing requires complex motor skills and fine adjustments to maintain balance in dynamic and challenging conditions. This study aimed to understand whether the balance ability in unspecific (UST) and sport-specific (SST) tasks could depend on the skiers’ ranking level. The balance performance of the dominant and non-dominant limbs in the SST was also investigated. Methods: Twenty-five skiers (14.96±1.61 yrs; 1.69±0.69 m; 59.9±9.52 kg) were divided into high-ranking (position<50) and low-ranking (position>50) groups. Subjects performed three balance conditions: static (ST), dynamic UST, and dynamic SST. Subjects stood on an unstable board over a force platform during UST. During SST, subjects wore ski boots, grasped ski poles, and each foot was clipped to an unstable board over two force plates. From the center-of-pressure (CoP) trajectory the area of the 95th percentile ellipse and the CoP mean velocity were calculated. Angular displacements were recorded by a 12-camera system, to calculate the full balance (FB), fine (FiB), and gross (GB) balance in UST and SST. Results: balance control was higher (p<0.01) in high-ranking than low-ranking skiers only in the SST. Kinematic parameters (i.e., FB, FiB, and GB) showed a higher (p<0.001) balance performance in SST than UST independently from the group. Dominant and non-dominant limbs motion was similar (Pearson correlation, r=0.97) in SST independently from the skiers’ ranking. Conclusion: high-ranking skiers showed better balance control and performance than low-ranking skiers only when the task was sport-specific. Therefore, we suggest testing balance under sport-specific conditions to discriminate the youth skiers’ abilities.